1997
DOI: 10.1074/jbc.272.24.15154
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Domains Conferring Ligand Binding Specificity to the Prostanoid Receptor

Abstract: To identify domains conferring ligand binding specificity to prostanoid receptors, we constructed a series of chimeric receptors by successively replacing the regions from the carboxyl-terminal tail of mouse prostacyclin (prostaglandin I (PGI)) receptor (mIP) with the corresponding regions of the mouse PGD receptor (mDP showed no affinity for the mIP, mDP, and all the chimeric receptors. These results suggest that the sixth to seventh transmembrane domain of the mIP receptor confers the specificity of this rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
31
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 34 publications
7
31
1
1
Order By: Relevance
“…Likewise, with CCK B R, both EC2 and EC3 were important for the CCK affinity (Silvente-Poirot et al, 1998). In contrast, only the TM3 region of the mouse PGD receptor was essential for prostaglandin D 2 binding (Kobayashi et al, 1997). These results demonstrate the marked variability in molecular determinants not only for different unrelated receptors but also for closely related receptors for peptide agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, with CCK B R, both EC2 and EC3 were important for the CCK affinity (Silvente-Poirot et al, 1998). In contrast, only the TM3 region of the mouse PGD receptor was essential for prostaglandin D 2 binding (Kobayashi et al, 1997). These results demonstrate the marked variability in molecular determinants not only for different unrelated receptors but also for closely related receptors for peptide agonists.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here support this hypothesis and suggest that a similar interaction between Lys-209 and the carboxylate of PGD 2 may occur. This would further differentiate the CRTH2 receptor from other prostanoid receptors, for which it has been suggested that TM VI and VII are responsible for recognition of the prostaglandin ␣-chain and terminal carboxylate by the DP and IP receptors (37) and that a conserved arginine in TM VII in the TP (38) and EP3 receptors (23,39) Interactions between the receptor and cyclopentyl ring substituents of prostaglandin ligands are thought to determine the ligand selectivity of each receptor. For the DP receptor, residues in TM I and II have been demonstrated to confer high affinity and selectivity of PGD 2 binding, suggesting that the cyclopentyl ring of PGD 2 is positioned next to TM I and II (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, with peptide agonists for the B 2 bradykinin receptor (63), the corticotropin-releasing factor receptor (69), or -and ␦-opioid receptors (70), the transmembrane regions are not important. In similar fashion, several nonpeptide agonists have been shown to primarily interact with GPCR upper transmembrane regions including nonpeptide agonists for adrenergic receptors (54,55), muscarinic cholinergic receptors (56,71,72), or eicosanoid (73,74). High affinity receptor binding of some peptide antagonists also have been shown to depend primarily on interaction with the upper transmembrane domains of receptors such as the interaction of NPC567 and Hoe140 with the B 2 bradykinin receptor (57,58) or BQ-123 with the ET A -R (13), whereas with other GPCRs such as interaction of CCK-JMV179 with the CCK-A receptor (12), the upper transmembrane regions are not important.…”
Section: Wild-type Nmbr and Grpr-thementioning
confidence: 99%